A fermented bean flour extract downregulates LOX-1, CHOP and ICAM-1 in HMEC-1 stimulated by ox-LDL. Issue 1 (December 2016) - Gabriele, Morena; Pucci, Laura; La Marca, Margherita; Lucchesi, Daniela; Della Croce, Clara; Longo, Vincenzo; Lubrano, Valter
Abstract This study focused on an extract from fermented flour from theLady Joy variety of the common beanPhaseolus vulgaris . The extract, Lady Joy lysate (Lys LJ), is enriched in antioxidant compounds during the fermentation. We assessed it for its protective effect on endothelial cells treated with oxidized-LDL (ox-LDL). The oxidative stress was determined by measuring the contents of thiobarbituric acid-reactive substances and reactive oxygen metabolites. ICAM-1, ET-1 and IL-6 concentrations were assessed using ELISA. LOX-1 and CHOP expression were analyzed using both quantitative RT-PCR and ELISA or western blotting. Ox-LDL treatment induced significant oxidative stress, which was strongly reduced by pre-treatment with the extract. The ox-LDL exposure significantly enhanced ICAM-1, IL-6 and ET-1 levels over basal levels. Lys LJ pre-treatment exerted an inhibitory effect on ox-LDL-induced endothelial activation with ICAM-1 levels comparable to those for the untreated cells. IL-6 and ET-1 production, although reduced, was still significantly higher than for the control. Both LOX-1 and CHOP expression were upregulated after ox-LDL exposure, but this effect was significantly decreased after Lys LJ pre-treatment. Lys LJ alone did not alter the ICAM-1, IL-6 and ET-1 concentrations or CHOP expression, but it did significantly lower the LOX-1 protein level. Our data suggest that Lys LJ is an effective antioxidant that is able to inhibit the oxidation process, but that it is only marginally active against inflammation and ET-1 production in HMEC-1 exposed to ox-LDL.